First description and expression analysis of tumor necrosis factor receptor-associated factor 6 (TRAF6) from the swimming crab, Portunus trituberculatus. Issue 2 (August 2015) - Zhou, Su-Ming; Li, Meng; Yang, Ning; Liu, Shun; Yuan, Xue-Mei; Tao, Zhen; Wang, Guo-Liang
Abstract: Tumor necrosis factor receptor-associated factor 6 (TRAF6) is a cytoplasmic adapter protein that mediates signals induced by the tumor necrosis factor receptor (TNFR) superfamily and the interleukin-1 receptor (IL-1R). In the present study, the full-length cDNA of TRAF6 (Pt-TRAF6) was identified in a marine crab, Portunus trituberculatus . Pt-TRAF6 ORF is predicted to encode a 599-amino acid protein, including a RING type zinc finger, two TRAF-type zinc fingers, and a meprin and TRAF homology (MATH) domain. The overall amino acid sequence identity between Pt-TRAF6 and other TRAF6s ranged from 50.9 to 51.3% for shrimp and from 16.1 to 19.4% for insects. The Pt-TRAF6 gene contains six exons and five introns, which is different from the organization of the insect TRAF6 gene. Pt-TRAF6 transcripts were broadly expressed in all tissues tested, and their expression was higher in hemocytes, gills, the intestine, and heart than in muscle. Interestingly, the level of Pt-TRAF6 transcript differed between male and female crabs. After Vibrio alginolyticus or lipopolysaccharide (LPS) challenge, the Pt-TRAF6 transcript was down-regulated in hemocytes and up-regulated in gills. Moreover, Pt-TRAF6 expression was altered sooner in the LPS challenge group than in the V. alginolyticus challenge group. These results indicate that Pt-TRAF6 may respond to Gram-negative bacterial infections. Highlights: Full-length cDNA of Pt-TRAF6 was cloned from Portunus trituberculatus. The level of Pt-TRAF6 transcript differed between male and female crabs. Pt-TRAF6 transcript was down-regulated in hemocytes and up-regulated in gills to Vibrio alginolyticus or LPS challenge.